Challenges Faced by PPNS, BPOM, and the Indonesian National Police in Addressing Illegal Cosmetic Cases in Gorontalo - Mohamad, Meliyanti; Yutye Imran, Suwito; Z. Mamu, Karlin (Universitas Negeri Gorontalo, 2024)
This study aims to examine the roles of PPNS investigators, BPOM, and the Indonesian National Police (Polri) in addressing the crime of illegal cosmetic distribution in Gorontalo, as well as the challenges faced by PPNS BPOM and Polri investigators in handling such cases. This research is an empirical legal study conducted at the Balai Besar Pengawas Obat dan Makanan (BPOM) office in Gorontalo and the Gorontalo City Police Station (Polresta Gorontalo Kota). The data sources for this study include both primary and secondary data. Data collection techniques involved interviews and data gathering. The collected data were then analyzed descriptively using qualitative methods. The research findings indicate that, firstly, the role of PPNS BPOM, particularly within the BPOM agency, encompasses the authority to conduct investigations and inquiries into cosmetic-related violations. However, they do not possess the authority to carry out arrests. In contrast, Polri investigators are responsible for executing legal actions such as arrests, detentions, searches, and the seizure of evidence. Additionally, they serve as coordinators in the investigation of specific cases. Secondly, the challenges faced by PPNS BPOM include a shortage of investigators, with only two personnel available, which hinders the investigative process. Meanwhile, Polri investigators encounter limitations due to inadequate laboratory facilities, which impede investigations that require laboratory-verified evidence.